Fabrication of WO3 Nanocone Arrays for Highly Sensitive C2H6 Gas Sensor Integrated with Low Powered in Plane Microheater - Adib, Md Ridwan; Lee, Keekeun (Proceedings of the IEEE International Conference on Micro Electro Mechanical Systems (MEMS), 2020)
The approaches of inexpensive and nanostructured metal oxide semiconductors are widely used for gas sensing. Among them, Tungsten Oxide (WO3) has attracted a lot of attentions due to its high sensitivity, structural simplicity, low cost production and high compatibility with nano-fabrication. However, thin film based planar WO3 has a limitation to enhance the sensitivity due to lower surface to volume ratio. To find improvements in sensor sensitivity and response time in terms of cone geometries and to determine optimal driving temperature for ethane (C2H6) gas sensor, hereby this paper reports, for the first time, the nanocone configured WO3 array combined with integration of low powered in-plane microheater.
Keywords: Cone geometry; High sensitivity; Microheater; Nanocone arrays; Nanostructured metals; Sensor sensitivity; Surface-to-volume ratio; Tungsten oxide; C2H6 sensor; In-plane microheater; WO3 nanocone